Caracteristici ale subocupării populației rurale - Mihalache, Flavius (Calitatea Vieții, 2014)
In the context of the Romanian rural economic life we have to conceptualize the employment status of the population not as a dichotomy of employed – not employed, but as a more substantial classification from adequate employment to inadequate employment. A substantial part of the employed population is facing an ambigous status: they are working in their oun households or in the agricultural sector. In the official statistics, these persoans are considered as working people, but, in fact, they represent a vast category of under-employed persons. Starting from this observation, this paper aims to explore the dimension of the Romanian rural underemployment, focusing on its coordinates and evolution, in the last period of time. The actual structure of the rural economic life determines an unbalanced distribution of the workforce, with a massive sector of the population working in agriculture. The main data show that, during the economic crisis, the sector of the rural population working in non-farming sectors decreased after 2008. In the same time, the farming sector had a more stable evolution, showing, in the last years, a tendency for growth. The sector of underemployed persons continues to be the dominant one in the rural workforce. This category includes more than 2.5 million persons which have an ambigous employment status, being unable to find a permanent job or to develop viable entrepreneurial initiatives. This category of persons presents key aspects of social and economic vulnerability, with all the negative aspects which emerge from these.